2006
DOI: 10.1136/bmj.38965.375718.80
|View full text |Cite
|
Sign up to set email alerts
|

Self management of arthritis in primary care: randomised controlled trial

Abstract: Objective To evaluate clinical effectiveness of a self management programme for arthritis in patients in primary care with osteoarthritis. Design Randomised controlled trial. Setting 74 general practices in the United Kingdom. Participants 812 patients aged 50 and over with osteoarthritis of hips or knees (or both) and pain or disability (or both). Intervention Participants were randomised to six sessions of self management of arthritis and an education booklet (intervention group) or the education booklet alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
198
1
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(213 citation statements)
references
References 21 publications
8
198
1
6
Order By: Relevance
“…A majority of these motivated participants increased in self-efficacy. Motivational problems were also detected in other studies [7].…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…A majority of these motivated participants increased in self-efficacy. Motivational problems were also detected in other studies [7].…”
Section: Discussionsupporting
confidence: 48%
“…Effects of the ASMP on self-efficacy, health behaviors, health status, and health care utilization have been documented in many studies [2][3][4][5]. However, at least two studies with primary care patients reported limited results [6,7]. In general, the effects of patient education programs for adults with RA are robust but short lived [8].…”
Section: Introductionmentioning
confidence: 99%
“…3,7 However, analyses of the impact of baseline self-efficacy and health have not been reported previously. It is also suggested that other research teams who have undertaken recent trials of chronic disease selfmanagement courses 7,11 investigate whether the present results can be replicated.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…3,4 Further trials of the course have recruited patients with a self-defined long-term condition, 5 adapted the generic programme to specific cultures, [6][7][8][9][10] and tested condition-specific adaptations. [11][12][13] A recently completed randomised controlled trial of the Expert Patients Programme showed it was effective in improving subjective measures of health, including a medium effect on self-efficacy (confidence in managing the effects of long-term conditions; effect size = 0.4), and small effects on energy (effect size = 0.2) and health-related quality of life (providing the equivalent of one extra week of perfect health per year). 5 These findings accorded with previous trials of the Stanford course.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis with eleven studies and three other randomized controlled trials (not included in this meta-analysis) undertaken in Sweden, France and in the United Kingdom (UK), showed limited improvement in pain and function. The UK study showed no superiority of a self-management course when an educational booklet was given [10][11][12][13]. However, it is feasible in a primary care setting and it can improve self-perceived health as well as function and a structured consultation program for patients with knee OA resulted in short term improvement in weight loss and time spent on physical activity [11,12].…”
Section: Introductionmentioning
confidence: 99%